A systematic review of validity evidence for checklists versus global rating scales in simulation‐based assessment. Issue 2 (February 2015) - Ilgen, Jonathan S; Ma, Irene W Y; Hatala, Rose; Cook, David A
<x xml:space="preserve">Abstract</x> Context The relative advantages and disadvantages of checklists and global rating scales (GRSs) have long been debated. To compare the merits of these scale types, we conducted a systematic review of the validity evidence for checklists and GRSs in the context of simulation‐based assessment of health professionals. Methods We conducted a systematic review of multiple databases including MEDLINE, EMBASE and Scopus to February 2013. We selected studies that used both a GRS and checklist in the simulation‐based assessment of health professionals. Reviewers working in duplicate evaluated five domains of validity evidence, including correlation between scales and reliability. We collected information about raters, instrument characteristics, assessment context, and task. We pooled reliability and correlation coefficients using random‐effects meta‐analysis. Results We found 45 studies that used a checklist and GRS in simulation‐based assessment. All studies included physicians or physicians in training; one study also included nurse anaesthetists. Topics of assessment included open and laparoscopic surgery (n = 22), endoscopy (n = 8), resuscitation (n = 7) and anaesthesiology (n = 4). The pooled GRS–checklist correlation was 0.76 (95% confidence interval [CI] 0.69–0.81, n = 16 studies). Inter‐rater reliability was similar between scales (GRS 0.78, 95% CI 0.71–0.83, n = 23; checklist 0.81, 95% CI 0.75–0.85, n = 21), whereas GRS inter‐item reliabilities (0.92, 95% CI 0.84–0.95, n = 6) and inter‐station reliabilities (0.80, 95% CI 0.73–0.85, n = 10) were higher than those for checklists (0.66, 95% CI 0–0.84, n = 4 and 0.69, 95% CI 0.56–0.77, n = 10, respectively). Content evidence for GRSs usually referenced previously reported instruments (n = 33), whereas content evidence for checklists usually described expert consensus (n = 26). Checklists and GRSs usually had similar evidence for relations to other variables. Conclusions Checklist inter‐rater reliability and trainee discrimination were more favourable than suggested in earlier work, but each task requires a separate checklist. Compared with the checklist, the GRS has higher average inter‐item and inter‐station reliability, can be used across multiple tasks, and may better capture nuanced elements of expertise.